Effect of Dividend Policy on Firm’s Performance: A Case Study of Cement Sector of Pakistan - Abdur Rahman (SEISENSE (PRIVATE) LIMITED, 2018)
The basic aim of this study is to investigate that whether the dividend policy makes an impact on the firm performance in Pakistan specially in cement sector. Data used have been collected from annual reports of the sample companies and website of Pakistan Stock Exchange from 2012 to 2016. The results of OLS indicate that there is an insignificant positive relationship between return on equity (ROE) and Dividend per share (D.P.S) which imply that by increasing cost dividend per share, return on equity increases for the selected companies. Furthermore, a significant positive relationship between earning per share (EPS) and return-on-equity (R.O.E) was found. In the case of firm size, significant relationship was found with ROE and financial leverage showed an insignificant relationship with firm performance (R.O.E). Hence this study supports the relevant theories of dividend policy.